2022
DOI: 10.1021/acsomega.2c04139
|View full text |Cite
|
Sign up to set email alerts
|

Just-in-Time Learning-Integrated Partial Least-Squares Strategy for Accurately Predicting 71 Chemical Constituents in Chinese Tobacco by Near-Infrared Spectroscopy

Abstract: Near-infrared spectroscopy has been widely used to characterize the chemical composition of tobacco because it is fast, economical, and nondestructive. However, few predictive models perform ideally when applied to large spectral libraries of tobacco and its various chemical indicators. In this study, the just-in-time learning-integrated partial least-squares (JIT-PLS) modeling strategy was applied for the first time to quantitatively analyze 71 chemical components in Chinese tobacco. Approximately 18000 tobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…Raman and infrared spectroscopies have been applied for an increasing number of use cases. Among others, these applications of spectroscopy include food, pharmaceuticals, cosmetics, tobacco, and nuclear waste. , In 2004, the US Food and Drug Administration (FDA) and the International Council for Harmonization (ICH) established an initiative to apply process analytical technologies (PAT), including spectroscopic PAC, for manufacturing quality assurance. , Many studies have reported on the use of spectroscopic analyzers, such as infrared (IR) and Raman, to monitor various stages of pharmaceutical manufacturing. ,, Spectroscopic PAT is useful both for real-time release and model predictive control. ,,, The linking of PAT to continuous manufacturing for real-time optimization and control using artificial intelligence was referred to by Price et. al as the “holy grail” …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Raman and infrared spectroscopies have been applied for an increasing number of use cases. Among others, these applications of spectroscopy include food, pharmaceuticals, cosmetics, tobacco, and nuclear waste. , In 2004, the US Food and Drug Administration (FDA) and the International Council for Harmonization (ICH) established an initiative to apply process analytical technologies (PAT), including spectroscopic PAC, for manufacturing quality assurance. , Many studies have reported on the use of spectroscopic analyzers, such as infrared (IR) and Raman, to monitor various stages of pharmaceutical manufacturing. ,, Spectroscopic PAT is useful both for real-time release and model predictive control. ,,, The linking of PAT to continuous manufacturing for real-time optimization and control using artificial intelligence was referred to by Price et. al as the “holy grail” …”
mentioning
confidence: 99%
“… 3 Raman and infrared spectroscopies have been applied for an increasing number of use cases. Among others, these applications of spectroscopy include food, 4 6 pharmaceuticals, 7 10 cosmetics, 11 tobacco, 12 and nuclear waste. 13 , 14 In 2004, the US Food and Drug Administration (FDA) and the International Council for Harmonization (ICH) established an initiative to apply process analytical technologies (PAT), including spectroscopic PAC, for manufacturing quality assurance.…”
mentioning
confidence: 99%